2021
DOI: 10.3389/fmicb.2021.662764
|View full text |Cite
|
Sign up to set email alerts
|

Free Chlorine and Peroxynitrite Alter the Capsid Structure of Human Norovirus GII.4 and Its Capacity to Bind Histo-Blood Group Antigens

Abstract: Human noroviruses (HuNoVs) are one of the leading causes of acute gastroenteritis worldwide. HuNoVs are frequently detected in water and foodstuffs. Free chlorine and peroxynitrite (ONOO−) are two oxidants commonly encountered by HuNoVs in humans or in the environment during their natural life cycle. In this study, we defined the effects of these two oxidants on GII.4 HuNoVs and GII.4 virus-like particles (VLPs). The impact on the capsid structure, the major capsid protein VP1 and the ability of the viral caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Hemoglobin and heme are primarily toxic to viruses due to the NOS and RNS produced by nitrification and oxidation, respectively. The ability of human norovirus GII.4 to bind tissue blood group antigens is altered by the presence of free chlorine and peroxynitrite [112] . WhiB1 is a NO-responsive Wbl protein (Actinomyces iron-sulfur protein), and nitrosylation of the iron-sulfur cluster permits positively charged residues in the C-terminal helix to participate in DNA binding [113] .…”
Section: Domains Of S Protein For Polyphenol Binding and Nitrificatio...mentioning
confidence: 99%
“…Hemoglobin and heme are primarily toxic to viruses due to the NOS and RNS produced by nitrification and oxidation, respectively. The ability of human norovirus GII.4 to bind tissue blood group antigens is altered by the presence of free chlorine and peroxynitrite [112] . WhiB1 is a NO-responsive Wbl protein (Actinomyces iron-sulfur protein), and nitrosylation of the iron-sulfur cluster permits positively charged residues in the C-terminal helix to participate in DNA binding [113] .…”
Section: Domains Of S Protein For Polyphenol Binding and Nitrificatio...mentioning
confidence: 99%
“…Hypochlorous acid (HOCl; p K a = 7.54) is regarded as the FAC species responsible for disinfection; HOCl inactivates viruses by oxidizing viral components. , Previous work suggests that viral inactivation can be driven by reactions involving proteins or nucleic acids. For example, Nuanualsuwan et al concluded that poliovirus inactivation by FAC is driven by genome damage, whereas Wigginton and Kohn concluded that bacteriophage MS2 inactivation by FAC could be attributed to reactions with the genome and capsid proteins . These differences in mechanisms may be driven by the virus structure, including the accessibility of highly reactive regions of the proteins and nucleic acids to FAC.…”
Section: Introductionmentioning
confidence: 99%